Interactions of relativistic particles in stellar winds - del Palacio, Santiago (2015)
Several binary systems hosting a massive star and a companion thatis either a similar star or a compact object, present non-thermal emission from radio to gamma-rays. This non-thermal emission is the consequence of the interactions of relativistic particles surrounded by the stellar wind. The main goal of this workis to characterize the high-energy physics of gamma-ray binaries by implementing ageneral modeling for their most important high-energy processes. To thoroughly investigate the effects of the emitter-star-observer geometry on the resultin gradiation, we sistematically applied a non-thermal leptonic model for different locations of the emitter, magnetic fields, and acceleration timescales. The results of this procedure are presented in the form of emissivity maps, which are usefulfor exploring statistical properties of gamma-ray binaries as well as their expected distribution in the galaxy.